Acidic deoxycholic acid and chenodeoxycholic acid induce interleukin‐8 production through p38 mitogen‐activated protein kinase and protein kinase A in a squamous epithelial model. Issue 5 (25th April 2013) - Shan, Jing; Oshima, Tadayuki; Fukui, Hirokazu; Watari, Jiro; Miwa, Hiroto
Abstract Background and Aim Immune‐mediated mucosal inflammation characterized by the production of interleukin (IL)‐8 is associated with the development of gastroesophageal reflux disease. The effects of bile acids, which are major components of reflux fluid, on the production of IL‐8 and related mechanisms remain unclear. This study aimed to address these questions using an esophageal stratified squamous epithelial model. Methods Normal human esophageal epithelial cells were seeded on the Transwell inserts and cultured with the air‐liquid interface system to establish the model. Bile acids under different pH conditions were added to the apical compartment to examine their effects on IL‐8 production and the underlying cellular signaling. Results Conjugated bile acids under a neutral or acidic condition did not induce IL‐8 production, and unconjugated bile acids, deoxycholic acid (DCA), and chenodeoxycholic acid (CDCA) all significantly induced IL‐8 production, dose‐ and time‐dependently, only under weakly acid conditions. Inhibition of p38 mitogen‐activated protein kinase (p38 MAPK) and protein kinase A (PKA) attenuated the production of IL‐8 induced by acidic DCA and CDCA. Inhibition of PKA did not block the bile acid‐induced p38 MAPK activation. Conclusions Compared with conjugated bile acids, the unconjugated bile acids DCA and CDCA are more likely to induce IL‐8 production in vivo, especially under weakly acid conditions. This process involves two independent signaling pathways, p38 MAPK and PKA.